The Mediatization of Interpretations of Family-Related Verses on Instagram: An Analysis of Authority, Reduction of Meaning, and Media Logic on the @keluargahamzi Account - Syamsul Ma'arif Ilyas; Muh. Alimin; Harel Bayu Paizin; Ahmad Tri Muslim HD (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2026)
This article examines the mediatization of interpretations of family-related verses on the Instagram account @keluargahamzi in the context of the transformation of interpretive authority on social media. Previous studies on digital interpretation have generally focused on social media da’wah, the “living Qur’an,” and the popularization of religion; however, few have highlighted how media logic shapes the reduction, simplification, and reframing of the meanings of family-related verses in the digital space. This research employs a qualitative content analysis approach using Stig Hjarvard’s framework of religious mediatization, integrated with an epistemological perspective on interpretation. The research data consists of posts from the @keluargahamzi account from 2019 to 2023 that feature family-related verses in the form of images, captions, and video reels. The data were analyzed through a process of thematic categorization, identification of patterns of interpretive simplification, and analysis of the relationship between Instagram’s media features and the construction of verse meanings.The findings reveal that the mediatization of interpretation on the @keluargahamzi account occurs through three primary patterns: the symbolic visualization of verses, the simplification of interpretive contexts, and the normative framing of the Islamic family. First, family-related verses are visually represented through domestic symbols that align with Instagram’s aesthetic logic. Second, interpretations tend to emphasize literal meanings and practical moral lessons while downplaying historical dimensions, asbāb al-nuzūl, and the complexity of classical exegesis. Third, Instagram features such as Reels, captions, and hashtags function as tools for meaning production as well as new digital interpretive authorities. This study demonstrates that social media not only serves as a channel for disseminating interpretations but also shapes how verses are understood, negotiated, and popularized within the digital public sphere.